Design, user experience, and usability. 4th International Conference, DUXU 2015, held as part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings /: 4th International Conference, DUXU 2015, held as part of HCI International 2015, Los Angeles, CA, USA, August 2-7, 2015, Proceedings. Interactive experience design : Part III, (2015) - Unknown
No abstract available